Weight gain after STN-DBS: The role of reward sensitivity and impulsivity. (July 2017) - Aiello, Marilena; Eleopra, Roberto; Foroni, Francesco; Rinaldo, Sara; Rumiati, Raffaella I.
Abstract: Weight gain has been reported after deep brain stimulation of the subthalamic nucleus (STN-DBS), a widely used treatment for Parkinson's disease (PD). This nucleus has been repeatedly found to be linked both to reward and to inhibitory control, two key aspects in the control of food intake. In this study, we assessed whether weight gain experienced by patients with PD after STN-DBS, might be due to an alteration of reward and inhibitory functions. Eighteen patients with PD were compared to eighteen healthy controls and tested three times: before surgery, in ON medication and after surgery, respectively five days after the implantation in ON medication/OFF stimulation and at least three months after surgery in ON medication/ON stimulation. All participants were assessed for depression (Beck Depression Inventory), anhedonia (Snaith-Hamilton Pleasure Scale) and impulsiveness (Barratt Impulsiveness Scale). They performed a battery of tests assessing food reward sensitivity (Liking, Wanting and Preference) and a food go/no-go task. Results showed that body weight significantly increased after STN-DBS. A few days after surgery, patients were slower and more impulsive in the go/no-go task, showed a higher preference for high calorie (HC) foods and rated foods as less tasty. Months after subthalamic stimulation, the performance on the go/no-go task improved while no differences were observed in reward sensitivity. Interestingly, weight gain resulted greater in patients with higher levels of attentional impulsiveness pre-surgery, higher wanting for low calorie (LC) foods and impulsivity in the go/no-go task in ON medication/ON stimulation. However, only wanting and attentional impulsivity significantly predicted weight change. Furthermore, weight gain resulted associated with the reduction ofl -Dopa after surgery and disease's duration. In conclusion, our findings are consistent with the view that weight gain in PD after STN-DBS has a multifactorial nature, which reflects the complex functional organization of the STN.